THE SECOND REGULARIZED TRACE FORMULA FOR THE STURM-LIOUVILLE OPERATOR - Akgun, F. Aydin; Bayramoglu, M.; Bayramov, A. (UNIV MISKOLC INST MATH, 2019)
In this paper, the second regularized trace formula for the differential operator with antiperiodic boundary conditions is obtained.
Keywords: eigenvalue; eigenfunction; resolvent; regularized trace; Mathematics